Anticancer Effect of Salvia plebeia and Its Active Compound by Improving T-Cell Activity via Blockade of PD-1/PD-L1 Interaction in Humanized PD-1 Mouse Model - Choi, Jang-Gi; Kim, Young Soo; Kim, Ji Hye; Kim, Tae In; Li, Wei; Oh, Tae Woo; Jeon, Chang Hyun; Kim, Su Jin; Chung, Hwan-Suck (Frontiers in Immunology, 2020)
Immune checkpoint inhibitors, increasingly used to treat malignant tumors, are revolutionizing cancer treatment by improving the patient survival expectations. Despite the high antitumor efficacy of antibody therapeutics that bind to PD-1/PD-L1, study on small molecule-based PD-1/PD-L1 inhibitors is required to overcome the side effects of antibody therapeutics caused by their size and affinity. Herein, we investigated antitumor potential of Salvia plebeia R. Br. extract (SPE), which has been used as a traditional oriental medicine and food in many countries, and its components by the blockade of PD-1/PD-L1 interaction. SPE and its component cosmosiin effectively blocked the molecular interaction between PD-1 and PD-L1. SPE also inhibited tumor growth by increasing CD8+ T-cells in the tumor through the activation of tumor-specific T-cells in a humanized PD-1 mouse model bearing hPD-L1 knock-in MC38 colon adenocarcinoma tumor. This finding presents a preclinical strategy to develop small molecule-based anticancer drugs targeting the PD-1/PD-L1 immune checkpoint pathway.